Higher neutrophil to lymphocyte ratio is associated with renal dysfunction and cardiac adverse remodeling in elderly with metabolic syndrome - Zhu, Yuqi; Li, Gang; Laukkanen, Jari A.; Song, Xing; Zhang, Jing; Wei, Linping; Chen, Xinrui; Li, Yufeng; Liu, Cheng (Frontiers in Cardiovascular Medicine, 2022)
Background Previous studies have shown that metabolic syndrome (MetS) is associated with increased systemic inflammation and cardiac mortality in elderly subjects. However, information on the association of inflammation markers with cardiac adverse remodeling is limited in the elderly with MetS. Therefore, we investigated whether the inflammatory marker neutrophil/lymphocyte ratio (NLR) is associated with the cardiac adverse remodeling in Chinese elderly with MetS. Methods A total of 1,087 hospitalized Chinese elderly (aged ≥ 65 years) with MetS were collected retrospectively. The cross-sectional data of echocardiography and clinical parameters were compared among quartile NLR groups. Results In the elderly with MetS, higher quartile NLR (≥3.83) was found to be associated with male gender, older age, lower estimated glomerular filtration rate (eGFR), and cardiac left ventricular (LV) dilatation (all p <0.05). Conclusion Higher NLR is associated with male gender, older age, renal dysfunction, and cardiac adverse remodeling in Chinese elderly with MetS.